Do Not Pass Go - Hill, Kirkpatrick (New York Margaret K. McElderry Books, 2007)
When Deet's father is jailed for using drugs, Deet learns that prison is not what he expected, nor are other people necessarily the way he thought they were.
6 - 8
Keywords: Prisoners - Fiction; Fathers - Fiction; Family life - Fiction; Interpersonal relations - Fiction; Quotations - Fiction